Decision Support Systems for Determining the Best Santri at PPTQ Al Kaukab using Simple Additive Weighting Method - Prabowo, I Putu Deny Arthawan Sugih; Mufidianingsih, Hana; Fahlevi, Mohammad Reza (Faculty of Engineering and Computer Science, 2025)
A Decision Support System (DSS) is a tool developed to aid in making decisions that are more accurate, efficient, and well-organized, particularly when assessing several options using multiple criteria. This research designed a Decision Support System (DSS) utilizing the Simple Additive Weighting (SAW) method to identify the top-performing santri at PPTQ Al Kaukab. The purpose of the system is to enhance educational quality by objectively selecting exceptional students for acknowledgment. The assessment was based on seven weighted criteria, including attitude, attendance, academic performance, and rule violations. Data were collected from seven selected santri, and each was scored and normalized before being processed using the SAW method. The final ranking showed that A3 (Muhda Lutfa Azizah) achieved the highest score of 0.803, followed by A1 (Unifah) with 0.791, and A5 (Tasa) with 0.686. These results indicate that the SAW method is effective in delivering accurate, fair, and transparent recommendations, making it a reliable approach for structured decision-making in pesantren environments.